Pengaruh Kepercayaan Diri Terhadap Prestasi Belajar Matematika Siswa - Aini, Hanifatul; Mubarokah, Nur Lailatul; Yunita, Maria Magdalena Milla; Rahmwati, Shela; Marhaeni, Nafida Hetty (PT Literasi Nusantara Publisher, 2023)
The research aimed to determine the significant positive effect of self-confidence on mathematics learning achievements. This research was conducted in the junior high school of Rifa’iyyah 01 Sapuran in Wonosobo, Central Java. The population of this research was VIII grade, where the entire population was sampled in this research with total sampling techniques. The instrument used was a questionnaire of self-confidence as many as 25 questions item and the mathematic midterm exam scores of students that have met valid and reliable criteria. The data analysis used involves testing the prerequisites of analysis and conducting simple linear regression analysis. The research results indicate that (1) the Sig. value of 0.000 < 0.05, therefore H0 is rejected, meaning that there is a significant influence of self-confidence on student’s mathematics learning achievements; (2) the coefficient of determination (R Square) is 0.399, which means that self-confidence accounts for 39.9% of the variation in student’s learning achievement, while 60.1% is influenced by other variables not examined; and (3) the standardized coefficient beta value is 0.632, indicating that self-confidence has a strong and positive relationship with student’s mathematics learning achievement. This means that the higher the level of students’ self-confidence, the better their mathematics learning achievement. Additionally, it is known that the regression equation model is Y = 31.047 + 0.462X. This model indicates that students’ mathematics learning achievement consistently remains at 31.047 in the absence of self-confidence. However, for every 1% increase in self-confidence, students’ mathematics learning achievement increases by 0.462.